Phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation as well as preparation method and application of phenolic resin-based hollow mesoporous carbon microspheres

By catalyzing the reaction of resorcinol/formaldehyde and tetraethyl silicate in the water/alcohol system without surfactant, the phenolic resin-based hollow mesoporous carbon microspheres were prepared, and the solution was solved The problem of preparing large mesoporous carbon microspheres in the prior art has achieved simple operation and excellent performance.

CN119503760APending Publication Date: 2025-02-25SANMING UNIV +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311082451.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to prepare large mesoporous and easy to regulate phenolic resin-based hollow mesoporous carbon microspheres without the assistance of surfactants, and the preparation process is complicated, difficult to operate, and high raw material consumption.

Method used

Using a method based on accelerated condensation, in the presence of surfactant, resorcinol/formaldehyde and tetraethyl silicate are catalyzed in the water/alcohol system, and the reaction temperature is controlled at 35-120℃ to obtain silica Phenolic resin/silica microspheres were coated, carbonized and removed to obtain hollow mesoporous carbon microspheres.

Benefits of technology

It is realized that the hollow mesoporous carbon microspheres with large mesoporous and easy to regulate are prepared without surfactants. The operation is simple. The prepared carbon microspheres have good electrochemical properties and can be applied to multiple fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503760A_ABST
    Figure CN119503760A_ABST
Patent Text Reader

Abstract

The invention discloses phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation and a preparation method and application thereof, and belongs to the technical field of carbon material preparation, and the preparation method comprises the following steps: in the absence of a surfactant, resorcinol / formaldehyde and tetraethyl silicate react in a water / alcohol system at the temperature of 35-120 DEG C under the catalytic action of ammonia water to obtain phenolic resin-based hollow mesoporous carbon microspheres; and carbonizing the silicon dioxide coated phenolic resin / silicon dioxide microspheres, and removing silicon dioxide to obtain the hollow mesoporous carbon microspheres. The method is simple and convenient to operate, a surfactant does not need to be added, the prepared carbon microspheres have large mesopores and hollow structures, meanwhile, the morphology and the pore structure of the carbon microspheres can be effectively regulated and controlled, and the carbon microspheres are applied as electrode materials and have good electrochemical performance. The hollow mesoporous carbon microspheres can also be applied to the fields of electrode materials, molding compounds, adsorption materials, drug loading or catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon material preparation, and in particular to phenolic resin-based hollow mesoporous carbon microspheres based on an accelerated condensation method, and a preparation method and application thereof. Background Art

[0002] The shortage of resources and environmental pollution have brought severe challenges to mankind. In particular, the large-scale use of fossil energy has led to abnormal climate, intensified greenhouse effect, and destruction of vegetation, which has had a significant impact on human life. The development of renewable energy has proposed an important way to solve this problem. The storage and conversion of renewable energy is the key to achieving the widespread use of clean energy, so the development of high-performance storage devices is of great significance. Current energy storage devices include supercapacitors, lithium-ion batteries, etc. Carbon materials are an important component of electrode materials for energy storage devices and have a significant impact on the performance of energy storage devices. Porous carbon materials have good application prospects in many fields due to their unique properties, such as heat resistance, stability, good conductivity, and easy surface chemical modification. Hollow carbon microspheres (HCS), as a type of porous carbon material with a special structure, have been widely studied in the fields of energy storage, catalysis, adsorption, etc. due to their regular geometric morphology and suitable porosity. The various properties of HCS strongly depend on its structural characteristics, including appropriate size and cavity diameter, controllable shell thickness, good surface properties, rich pore structure, etc., so a lot of research has been carried out on the controllable preparation of HCS. In terms of pore structure, compared with microporous or non-porous materials, hollow mesoporous carbon microspheres (HMCS) have the advantages of low density, porous shell, larger cavity, easily accessible internal space, and large pore volume. Their applications in energy conversion and storage have received special attention.

[0003] The research on HMCS has a long history, and the preparation methods are diverse, mainly including hard template method and soft template method or a combination of the two. For example, the early hard template method uses silicon microspheres containing hard core mesoporous shells as templates, coats polymers, and obtains HMCS after carbonization and removal of the template. However, this method is limited in the scale of adjusting the pore structure, and the mesopore size is also small. The combination of hard and soft templates is currently a commonly used method for preparing HMCS. While adjusting the mesoporous structure, it can also achieve the regulation of the morphological structure, but the regulation of this structure depends heavily on surfactants.

[0004] For example, Fuertes et al. (Chem Commun (Camb) 48 (49) (2012) 6124-6126) added tetraethyl silicate (TEOS) and resorcinol / formaldehyde to a water / ethanol system at room temperature, obtained core-shell microspheres under the catalysis of ammonia water, and obtained hollow microporous microspheres after carbonization and removal of silica. The pore size was mainly concentrated below 2 nm, which was a microporous structure. By adding a surfactant to this system, mesopores with a pore size of 4.7 nm (Nano Lett 13 (1) (2013) 207-212) could be obtained. In order to prepare mesoporous carbon microspheres without surfactant, Zhang et al. successfully obtained multi-shell mesoporous (depressed) carbon microspheres by adding TEOS twice. The silica produced by the hydrolysis of high-concentration TEOS plays an important role in the generation of mesopores (Chemistry of Materials 27 (2015) 6297-6304). In addition, by replacing TEOS with TPOS, the specific surface area and mesopore diameter can be significantly improved (ACS Nano 10 (4) (2016) 4579-86). However, this method still has the disadvantages of complex process, difficult operation and high consumption of raw materials. At the same time, TPOS is expensive and not conducive to industrial production. Summary of the invention

[0005] In order to overcome the defects of the above-mentioned prior art, the technical problem to be solved by the present invention is to provide a method for preparing large-mesopore and easily controllable phenolic resin-based hollow mesoporous carbon microspheres without the assistance of surfactant, as well as the hollow mesoporous carbon microspheres prepared by the method, and the application of the hollow mesoporous carbon microspheres.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0007] A method for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation comprises the following steps: in the absence of a surfactant, resorcinol / formaldehyde and tetraethyl silicate react in a water / alcohol system under the catalytic action of aqueous ammonia at a temperature of 35-120° C. to obtain silica-coated phenolic resin / silicon dioxide microspheres, and the microspheres are carbonized and the silicon dioxide is removed to obtain hollow mesoporous carbon microspheres.

[0008] A phenolic resin-based hollow mesoporous carbon microsphere is prepared by the above-mentioned method for preparing phenolic resin-based hollow mesoporous carbon microsphere based on accelerated condensation.

[0009] Application of phenolic resin-based hollow mesoporous carbon microspheres in electrode materials, molding materials, adsorption materials, drug loading or catalysis.

[0010] Specifically, the present invention provides a method for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation, and the preparation steps are as follows:

[0011] 1) Add resorcinol to a water / alcohol system, add ammonia water, and stir evenly;

[0012] 2) adding formaldehyde and tetraethyl silicate, reacting at a temperature of 35-120° C. to obtain a turbid liquid;

[0013] 3) centrifuging, washing and drying the turbid liquid to obtain silica-coated phenolic resin / silica microspheres;

[0014] 4) The microspheres are carbonized and the silicon dioxide is removed to obtain hollow mesoporous carbon microspheres.

[0015] The beneficial effects of the present invention are as follows: the present invention is easy to operate, does not require the addition of surfactants, and the prepared carbon microspheres have large mesopores and hollow structures. At the same time, the size of the carbon microspheres and the size of the cavity, the thickness of the shell, and the diameter of the mesopores can be effectively regulated. When used as an electrode material, it has good electrochemical properties and can also be used in molding materials, adsorption materials, drug loading or catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 : SEM of silica-coated phenolic resin / silica core-shell microspheres prepared in Example 1;

[0017] Figure 2 : Schematic diagram of the structure of the silica-coated phenolic resin / silica microspheres in Example 1;

[0018] Figure 3 : Example 1 SEM of silica-coated carbon / silica core-shell microspheres;

[0019] Figure 4 : TEM of carbon microspheres (HMCS1) of Example 1;

[0020] Figure 5 : TEM of carbon microspheres (HCS) of Comparative Example 1. DETAILED DESCRIPTION

[0021] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in combination with the implementation modes and the accompanying drawings.

[0022] The key concept of the present invention is: by increasing the reaction temperature, accelerating the condensation rate of resorcinol / formaldehyde, reducing the time difference between the hydrolysis / condensation of resorcinol / formaldehyde and TEOS and the precipitation of microparticles, reducing the duration of TEOS homogeneous nucleation, promoting the co-assembly of TEOS hydrolysis condensation products and resorcinol / formaldehyde condensation products, and forming silica-coated phenolic resin / silicon dioxide (SiO2@SiO2 / RF) core-shell microspheres. During carbonization, the resin on the outer shell is converted into carbon, and the silica is still retained to obtain silica-coated carbon / silicon dioxide (SiO2@SiO2 / C) core-shell microspheres. After removing the silica in the inner core and the shell layer, hollow mesoporous carbon microspheres (HMCS) are obtained, in which the silica in the inner core acts as a hollow template and the silica in the shell layer acts as a mesoporous template.

[0023] Specifically, the present invention provides a method for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation. The specific preparation method is: in the absence of a surfactant, resorcinol / formaldehyde and tetraethyl silicate are reacted in a water / alcohol system under the catalytic action of ammonia water at a temperature of 35-120°C to obtain silica-coated phenolic resin / silica microspheres, and the microspheres are carbonized and the silica is removed to obtain hollow mesoporous carbon microspheres.

[0024] In the water / alcohol / ammonia system, the hydrolysis and condensation rate of tetraethyl silicate is significantly greater than the condensation rate of resorcinol-formaldehyde. Therefore, if tetraethyl silicate and resorcinol / formaldehyde are added to the water / alcohol / ammonia system together, tetraethyl silicate will rapidly hydrolyze and condense to form silica microspheres. When the resorcinol / formaldehyde condenses to a degree sufficient to precipitate phenolic resin particles, the tetraethyl silicate in the system has basically reacted to form silica microspheres. Therefore, the phenolic resin particles can only be coated on the surface of silica alone to form silica-coated phenolic resin microspheres. After carbonization and removal of the silica in the inner core, only hollow microporous carbon microspheres can be obtained (see Comparative Example 1). When the reaction temperature is increased, such as when the reaction temperature is increased to 35°C, on the one hand, the reaction rate of TEOS increases, and at the same time, the condensation rate of hydroquinone and formaldehyde also increases. However, our research found that the condensation of hydroquinone and formaldehyde is more sensitive to temperature. When the reaction temperature is increased, the difference between the hydrolysis condensation rate of tetraethyl silicate and the condensation rate of hydroquinone-formaldehyde will gradually decrease, which will lead to an increase in the concentration of tetraethyl silicate and its soluble condensation products in the later stage of the system. Therefore, the silica produced by homogeneous nucleation of TEOS in the early stage becomes the core. When the hydroquinone / formaldehyde resin begins to precipitate on the silica core particles, the hydrolysis / condensation products of the remaining TEOS in the system are in NH4 +Under the action of , it will be assembled and coated on the surface of silica core particles through heterogeneous nucleation mechanism with resorcinol / formaldehyde resin. In addition, the increase of reaction temperature will make the hydrolysis rate of TEOS greater than the condensation rate, so that there are more silica monomers in the system, which is conducive to its later co-assembly with phenolic resin to form a larger mesoporous structure.

[0025] As the reaction temperature is further increased, the difference between the hydrolysis condensation rate of tetraethyl silicate and the condensation rate of resorcinol-formaldehyde will be further reduced, which will allow more silica particles to be co-assembled with resorcinol-formaldehyde resin and increase the mesoporous pore size. Therefore, increasing the reaction temperature to 35-120°C is the key factor in obtaining the patented hollow mesoporous carbon microspheres of the present invention.

[0026] Furthermore, the present invention provides a method for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation, and the preparation steps are as follows:

[0027] 1) Add resorcinol to a water / alcohol system, add ammonia water, and stir evenly;

[0028] 2) adding formaldehyde and tetraethyl silicate, reacting at a temperature of 35-120° C. to obtain a turbid liquid;

[0029] 3) centrifuging, washing and drying the turbid liquid to obtain silica-coated phenolic resin / silica microspheres;

[0030] 4) The microspheres are carbonized and the silicon dioxide is removed to obtain hollow mesoporous carbon microspheres.

[0031] Furthermore, the alcohol is one or a combination of two or more of methanol, ethanol, propanol, butanol, octanol, pentanol, hexanol, heptanol, heptyl alcohol, ethylene glycol, glycerol, propylene glycol, and pentaerythritol, preferably ethanol.

[0032] Furthermore, the formaldehyde is paraformaldehyde or formaldehyde aqueous solution, preferably formaldehyde aqueous solution, and the molar ratio of formaldehyde to resorcinol is 1.5-3:1.

[0033] From the above description, it can be seen that the reaction rate of resorcinol and formaldehyde is significantly accelerated under the condition of more than 35°C, which can ensure that when resorcinol and formaldehyde condense to precipitate microparticles, there is still enough residual TEOS and its soluble condensate or monomer in the system. Therefore, TEOS is first hydrolyzed and condensed to produce silica microparticles in the early stage, which become the core. When resorcinol and formaldehyde condense to precipitate phenolic resin microparticles, they are co-assembled with the silica produced by the hydrolysis / condensation of the remaining TEOS and coated on the surface of the silica core, finally forming silica-coated phenolic resin / silica shell core microspheres (SiO2@SiO2 / RF), and silica-coated carbon / silica shell core microspheres (SiO2@SiO2 / C) are obtained after carbonization. After removing the silica in the core and shell, hollow mesoporous carbon microspheres (HMCS) are obtained, and the silica in the core acts as a hollow template, and the silica in the shell acts as a pore-forming role. If the reaction temperature is further increased, the reaction rate of resorcinol and formaldehyde will further increase. Although the hydrolysis / condensation rate of TEOS is also increased, the rate difference between them is reduced, which will allow more silica to be co-assembled with phenolic resin and coated on the surface of silica to form a thicker shell and larger mesopores. At the same time, with the increase in temperature, the size of the silica core will decrease due to the increase in nucleation rate, so that the size and cavity size of the final carbon microspheres are reduced. Therefore, the patented technology of the present invention can not only prepare hollow mesoporous carbon microspheres, but also achieve simple and effective regulation of the size and cavity size of the carbon microspheres, shell thickness, and mesopore diameter.

[0034] Furthermore, the volume ratio of water to alcohol is 1:1-10, preferably, the volume ratio of water to alcohol is 1:5-8.

[0035] Furthermore, the concentration of resorcinol in the solution is 1-100 mg / mL.

[0036] Furthermore, the molar ratio of the aqueous ammonia to resorcinol is 1-20:1.

[0037] From the above description, it can be seen that the ammonia water, in addition to the catalytic effect, also has the effect of reducing the surface polarity of silica, so that silica and phenolic resin can be better co-assembled and coated on the surface of silica to form a core-shell structure.

[0038] Furthermore, the molar ratio of tetraethyl silicate to resorcinol is 0.5-20:1.

[0039] As can be seen from the above description, tetraethyl silicate is an industrialized product with the best cost among all kinds of silicates. However, it is very difficult to select tetraethyl silicate as a template to prepare mesoporous carbon microspheres, especially under the condition of no surfactant, and the main structure formed is a microporous structure. This is mainly because at room temperature, especially in a water-alcohol system with a temperature below 35°C, the hydrolysis and condensation rate of tetraethyl silicate is very fast. Taking the system of Comparative Example 1 as an example, most of the tetraethyl silicate will be rapidly hydrolyzed and condensed within 140 minutes to form silica microspheres, while the condensation of resorcinol and formaldehyde has not yet formed phenolic resin particles. When the phenolic resin particles are precipitated at about 142 minutes, there is almost no remaining tetraethyl silicate and its soluble condensation products in the system, and the phenolic resin can only be coated on the surface of silica alone, and finally a microporous structure is formed, which is also the result that most existing literature can achieve. If the temperature is raised to 35°C (Example 1), the hydrolysis and condensation rate of tetraethyl silicate is accelerated, and the hydrolysis and condensation are basically completed in about 120 minutes. However, at this temperature, the condensation rate of resorcinol and formaldehyde increases significantly, and phenolic resin particles can be precipitated in about 60 minutes. Therefore, in this time period of 60-120 minutes, the phenolic resin will be co-assembled with silica to be coated on the surface of silica, forming a phenolic resin / silicon dioxide composite shell layer, and the mesoporous layer is obtained after carbonization and removal of silica. With the increase of temperature, the proportion of co-assembly time will be further increased, more silica will be co-assembled with phenolic resin, and with the increase of temperature, the size of the silica core will be reduced, so that the overall size and cavity will be smaller, the shell will be thicker, and the mesoporous pore size will be larger. Carbon microspheres are formed to achieve precise regulation.

[0040] Furthermore, the reaction temperature is 35-120°C, preferably, the reaction temperature is 45-80°C, and the reaction time is 15 min-1 h.

[0041] From the above description, it can be seen that at a higher reaction temperature, the nucleation rate is accelerated, so stable microspheres can be formed in a shorter time, and the reaction time can also be shortened, which is another advantage of the patent of the present invention, which can significantly improve the preparation efficiency and provide an effective path for the industrial preparation of large mesoporous hollow carbon microspheres. However, too high a reaction temperature will cause uneven ball formation, reduced sphericity, and too fine particles that are difficult to separate and disperse. The reaction temperature of the present invention is 35-120°C, preferably, the reaction temperature is 45-80°C, and the reaction time is 15min-1h. Increasing the reaction temperature and reducing the reaction time provide an effective path for the rapid preparation of mesoporous carbon microspheres.

[0042] Furthermore, the pore size of the hollow mesoporous carbon microspheres is greater than 10 nm. The present invention can be used to prepare carbon microspheres with large mesoporous pore sizes, and in particular, can achieve batch preparation of carbon microspheres with pore sizes greater than 10 nm, showing significant advantages.

[0043] Furthermore, carbonization can be carried out by methods well known to those skilled in the art, such as carbonization in a tube furnace or a muffle furnace. In order to improve the yield and maintain a good morphology, carbonization is preferably carried out under the protection of an inert gas, wherein the inert gas includes but is not limited to one of nitrogen, argon, and helium. The carbonization conditions can be selected from 500-1000°C for 1-6h.

[0044] Furthermore, the silicon dioxide may be removed by methods well known to those skilled in the art, such as soaking in hydrofluoric acid or alkali to remove the silicon dioxide.

[0045] Furthermore, the hollow mesoporous carbon microspheres are used in electrode materials, molding materials, adsorption materials, drug loading or catalysis. The patented method of the present invention has the advantages of simple preparation method, high efficiency and low cost. The prepared carbon microspheres have controllable size and pore size, and can be well applied in new energy, catalysis, new materials and other fields. For example, as electrode materials for supercapacitors and lithium-ion batteries, they show good electrochemical properties, as adsorption materials have good adsorption characteristics, and as raw materials for preparing new materials, they can show good nano-efficiency, improve material performance and reduce material specific gravity.

[0046] Example 1

[0047] 1) Add resorcinol to a water / ethanol system, add ammonia water (25%), and stir evenly;

[0048] 2) adding 37% formaldehyde aqueous solution and tetraethyl silicate, reacting at 35°C for 24 hours to obtain a turbid solution;

[0049] 3) centrifuging, washing and drying the turbid liquid to obtain silica-coated phenolic resin / silica microspheres;

[0050] 4) The microspheres were carbonized at 700°C for 4 h to obtain silica-coated carbon / silica core-shell microspheres, and hollow mesoporous carbon microspheres HMCS1 were obtained by removing silica with hydrofluoric acid.

[0051] Among them, the volume ratio of water to alcohol is 1:7;

[0052] The molar ratio of ammonia to resorcinol is 11:1;

[0053] The concentration of resorcinol in the solution was 5 mg / mL;

[0054] The molar ratio of formaldehyde to resorcinol is 2:1;

[0055] The molar ratio of tetraethyl silicate to resorcinol is 3.4:1;

[0056] The pore size of the carbon microspheres was found to be about 8.9 nm, and the BET specific surface area and pore volume were 712.2 m 2 g -1 and 2.4cm 3 g -1 .

[0057] Comparative Example 1

[0058] 1) Add resorcinol to a water / ethanol system, add ammonia water (25%), and stir evenly;

[0059] 2) adding 37% formaldehyde aqueous solution and tetraethyl silicate, reacting at 25°C for 24 hours to obtain a turbid solution;

[0060] 3) centrifuging, washing and drying the turbid liquid to obtain silica-coated phenolic resin / silica microspheres;

[0061] 4) The microspheres were carbonized at 700°C for 4 h to obtain silica-coated carbon microspheres, and hollow carbon microspheres HCS were obtained by removing silica with hydrofluoric acid.

[0062] Among them, the volume ratio of water to alcohol is 1:7;

[0063] The molar ratio of ammonia to resorcinol is 11:1;

[0064] The concentration of resorcinol in the solution was 5 mg / mL;

[0065] The molar ratio of formaldehyde to resorcinol is 2:1;

[0066] The molar ratio of tetraethyl silicate to resorcinol is 3.4:1;

[0067] The pore size of the carbon microspheres was less than 2 nm, and the BET specific surface area and pore volume were 514.3 m 2 g -1 and 1.2cm 3 g -1 .

[0068] Example 2

[0069] 1) Add resorcinol to a water / ethanol system, add ammonia water (25%), and stir evenly;

[0070] 2) adding 37% formaldehyde aqueous solution and tetraethyl silicate, reacting at 45°C for 24 hours to obtain a turbid solution;

[0071] 3) centrifuging, washing and drying the turbid liquid to obtain silica-coated phenolic resin / silica microspheres;

[0072] 4) The microspheres were carbonized at 700°C for 4 h to obtain silica-coated carbon / silica core-shell microspheres, and hollow mesoporous carbon microspheres HMCS2 were obtained by removing silica with hydrofluoric acid.

[0073] Among them, the volume ratio of water to alcohol is 1:7;

[0074] The molar ratio of ammonia to resorcinol is 11:1;

[0075] The concentration of resorcinol in the solution was 5 mg / mL;

[0076] The molar ratio of formaldehyde to resorcinol is 2:1;

[0077] The molar ratio of tetraethyl silicate to resorcinol is 3.4:1;

[0078] The pore size of the carbon microspheres was found to be about 10.9 nm, and the BET specific surface area and pore volume were 1236.4 m 2 g -1 and 2.6cm 3 g -1 .

[0079] Example 3

[0080] 1) Add resorcinol to a water / ethanol system, add ammonia water (25%), and stir evenly;

[0081] 2) adding 37% formaldehyde aqueous solution and tetraethyl silicate, reacting at 65°C for 0.5h to obtain a turbid solution;

[0082] 3) centrifuging, washing and drying the turbid liquid to obtain silica-coated phenolic resin / silica microspheres;

[0083] 4) The microspheres were carbonized at 700°C for 4 h to obtain silica-coated carbon / silica core-shell microspheres, and hollow mesoporous carbon microspheres HMCS3 were obtained by removing silica with hydrofluoric acid.

[0084] Among them, the volume ratio of water to alcohol is 1:7;

[0085] The molar ratio of ammonia to resorcinol is 11:1;

[0086] The concentration of resorcinol in the solution was 5 mg / mL;

[0087] The molar ratio of formaldehyde to resorcinol is 2:1;

[0088] The molar ratio of tetraethyl silicate to resorcinol is 3.4:1;

[0089] The pore size of the carbon microspheres was found to be about 12.5 nm, and the BET specific surface area and pore volume were 1239.9 m2 g -1 and 2.8cm 3 g -1 .

[0090] Example 4

[0091] 1) Add resorcinol to a water / ethanol system, add ammonia water (25%), and stir evenly;

[0092] 2) adding 37% formaldehyde aqueous solution and tetraethyl silicate, reacting at 120° C. for 30 min to obtain a turbid solution;

[0093] 3) centrifuging, washing and drying the turbid liquid to obtain silica-coated phenolic resin / silica microspheres;

[0094] 4) The microspheres were carbonized at 700°C for 4 h to obtain silica-coated carbon / silica core-shell microspheres, and hollow mesoporous carbon microspheres HMCS4 were obtained by removing silica with hydrofluoric acid.

[0095] Among them, the volume ratio of water to alcohol is 1:7;

[0096] The molar ratio of ammonia to resorcinol is 11:1;

[0097] The concentration of resorcinol in the solution was 10 mg / mL;

[0098] The molar ratio of formaldehyde to resorcinol is 2:1;

[0099] The molar ratio of tetraethyl silicate to resorcinol is 3.4:1;

[0100] The pore size of the carbon microspheres was found to be about 12.8 nm, and the BET specific surface area and pore volume were 1282.6 m 2 g -1 and 2.7cm 3 g -1 .

[0101] Supercapacitor performance test: The prepared carbon microspheres were mixed with binder PVDF and carbon black in a mass ratio of 8:1:1 and coated on an electrode sheet to obtain a working electrode. The performance was tested in the following way: On a CHI760E electrochemical workstation, a constant current charge and discharge test was performed using a 6M KOH electrolyte and a three-electrode system. The electrodes of the three-electrode system included a reference electrode (Hg / HgO), a counter electrode (Pt sheet) and a working electrode. The results are shown in Table 1.

[0102] Table 1 Supercapacitor performance test results

[0103]

[0104] It can be seen from Table 1 that the electrode prepared using the phenolic hollow mesoporous carbon microspheres obtained in the present invention as the material has a high capacity and capacity retention rate.

[0105] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation, characterized in that: In the absence of a surfactant, resorcinol / formaldehyde and tetraethyl silicate react in a water / alcohol system under the catalytic action of ammonia water at a temperature of 35-120°C to obtain silica-coated phenolic resin / silica microspheres, and the silica-coated phenolic resin / silica microspheres are carbonized and the silica is removed to obtain hollow mesoporous carbon microspheres.

2. The method for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation according to claim 1, characterized in that: The following steps are involved: 1) Add resorcinol to a water / alcohol system, add ammonia water, and stir evenly; 2) adding formaldehyde and tetraethyl silicate, reacting at a temperature of 35-120° C. to obtain a turbid liquid; 3) centrifuging, washing and drying the turbid liquid to obtain silica-coated phenolic resin / silica microspheres; 4) The microspheres are carbonized and the silicon dioxide is removed to obtain hollow mesoporous carbon microspheres.

3. A method for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation according to claim 1 or 2, characterized in that: The alcohol is one or a combination of two or more of methanol, ethanol, propanol, butanol, octanol, pentanol, hexanol, heptanol, decanol, ethylene glycol, glycerol, propylene glycol, and pentaerythritol. In the water / alcohol system, the volume ratio of water to alcohol is 1:1-10, preferably 1:5-8.

4. A method for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation according to claim 1 or 2, characterized in that: The formaldehyde is paraformaldehyde or formaldehyde aqueous solution, and the molar ratio of the formaldehyde to resorcinol is 1.5-3:

1.

5. The method for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation according to claim 1 or 2, characterized in that: The concentration of resorcinol in the solution is 1-100 mg / mL.

6. A method for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation according to claim 1 or 2, characterized in that: The molar ratio of the aqueous ammonia to resorcinol is 1-20:1, and the molar ratio of the tetraethyl silicate to resorcinol is 0.5-20:

1.

7. A method for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation according to claim 1 or 2, characterized in that: The temperature is preferably 45-80°C, and the reaction time is 15 min-1 h.

8. The method for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation according to claim 1, characterized in that: The average mesopore diameter of the hollow mesoporous carbon microspheres is greater than 10 nm.

9. A phenolic resin-based hollow mesoporous carbon microsphere, characterized in that: The hollow mesoporous carbon microspheres are prepared by any one of the methods for preparing phenolic resin-based hollow mesoporous carbon microspheres based on accelerated condensation as described in claims 1 to 8.

10. Use of the phenolic resin-based hollow mesoporous carbon microspheres according to claim 9 in the fields of electrode materials, molding materials, adsorption materials, drug loading or catalysis.

Citation Information

Cited By

  • Amplification preparation system for millimeter-scale mesoporous carbon spheres

    CN121493940A

  • Aluminum alloy conductor overhead insulated wire

    CN122213554A